SOEs as Borg Parties in the Event of Debtor Default and its Relationship to the Concept of State Losses - Gospel Bulo Pasulu; Delvino Aldy Djiwandono (Journal of Law, Politic and Humanities, 2024)
State-Owned Enterprises (BUMN) are one embodiment of the mandate of the Preamble to the 4th Paragraph of the 1945 Constitution of the Republic of Indonesia which mandates the promotion of public welfare. As a business entity that has a central role in the lives of Indonesian citizens, BUMN strives to continue to innovate and develop its business lines. In its efforts to develop a business, it is very common for a business entity to experience profits or losses as part of dynamic market fluctuations. BUMN is a business entity in which there is participation in shares by the Republic of Indonesia with a minimum of 51% (fifty one percent), Thus, when the BUMN experiences losses it will create a condition that is considered detrimental to state finances. This research aims to analyze the classification of the concept of state losses within the scope of business activities in BUMN, especially in the case of BUMN as the Guarantor/Borg using a statutory approach, conceptual approach and case approach. The results of this research are that there are certain indicators and benchmarks in determining whether losses experienced by BUMN can be classified as acts that are detrimental to the state or merely a business risk caused by external factors.